The Japanese occupation and the peculiarity of Philippine nationalism - Aguja, Hilton J. (Langkit : the Official journal of the College of Arts & Social Sciences Mindanao State University-Iligan Institute of Technology, 2010)
Historical accounts of the Philippine experience with the Japanese occupation have inordinately emphasized the commission of war crimes and other despicable atrocities against the native population. This depiction may contain some kernel of truth, but it is not the entire story.